Performance measurement using balanced scorecard-reinsurance industry in Malaysia and Singapore / Tan Siew Pei - Tan, Siew Pei (2012)
This paper aims to examine the performance measurement using the balanced scorecard in reinsurance industry in Malaysia and Singapore. It investigates the relationships of the four perspectives of balanced scorecard toward performance measurement. The purpose of this paper is to access whether improvement of the cause-and-relationship of the non-financial measures will lead to the improvement of financial measures. To test these relationships, data were collected using the four perspective approach introduced by Kaplan and Norton. The finding indicates that the financial measure is not significant to performance measurement and reinsurance industry has put greater emphasis to non-financial measures. The results also reveals that increase of customers’ satisfaction will not lead to the improvement of the financial performance. At the end of the article, there are some implications for reinsurance industry and some suggestions for the future studies.